HYDROTALCITES: RELATION BETWEEN STRUCTURAL FEATURES, BASICITY AND ACTIVITY IN THE WITTIG REACTION - Sychev M.; Prihod'ko R.; Erdmann K.; Mangel A.; Van Santen R.A. (My University, 2001)
Carbonate hydrotalcites (HTls) were prepared by coprecipitation of metal nitrate salts and Na2CO3. The structural features of noncalcined, calcined and reconstructed materials were characterized by XRD, 27Al MAS NMR, AAS and N2 adsorption. It was shown that reconstruction of the calcined HTls due to a memory effect results in the formation of materials with structural and surface features different from those of the parent hydrotalcites.Hydrotalcites can efficiently catalyze the liquid-phase synthesis of alkenes following the Wittig reaction. The optimum activity was found for materials with the Al/(Al+M2+) molar ratio of 0.20–0.26. Their selectivity can be controlled by a proper choice of pretreatment conditions, such as calcination and structural reconstruction. The solvent composition influences both the reaction rate and catalyst selectivity. The Z- and E-alkenes can be obtained with a high yield. The applicability of HTls for the Wittig reaction is limited by the pKa and composition of the ylide precursor. The Wittig reaction is sensitive to the structure of the basic catalyst when a moderate acid, such as Ph3P+CH2CO2Et with pKa=8.8, is used as the ylide precursor.